If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46.9 + -3x = 26 + 8x Solving 46.9 + -3x = 26 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 46.9 + -3x + -8x = 26 + 8x + -8x Combine like terms: -3x + -8x = -11x 46.9 + -11x = 26 + 8x + -8x Combine like terms: 8x + -8x = 0 46.9 + -11x = 26 + 0 46.9 + -11x = 26 Add '-46.9' to each side of the equation. 46.9 + -46.9 + -11x = 26 + -46.9 Combine like terms: 46.9 + -46.9 = 0.0 0.0 + -11x = 26 + -46.9 -11x = 26 + -46.9 Combine like terms: 26 + -46.9 = -20.9 -11x = -20.9 Divide each side by '-11'. x = 1.9 Simplifying x = 1.9
| 5+(4+y)= | | -15-2x=12+x | | r^2+12r+36+r^2=81 | | (x^3+2x+2)(x^2-x-1)= | | -32+7x=16+4x | | 7x-8(x+3)=14 | | 4-[(5-9)-2]= | | 5+2x+x=3x-3+8 | | 25x=480 | | -4=-(x+9) | | x-61=-3x+23 | | 6x-14=-2(8x+x) | | 231.34x=2082.06 | | (2x^2+5x+5)(4x-3)= | | -134-5x=8x+35 | | 2x-3/x-4=2/3 | | 3q^2-2q-16=9 | | 4k-15+7k-48= | | 5xu=12 | | 7v-4=5v+10 | | f(x)=-16x^2+64x | | H(t)=160t-10t^2 | | 23c=207 | | 3(6y-1)-(8y-6)= | | (11n+3)(2n-5)=0 | | -39-x=4x+71 | | 32.54m=292.86 | | -12-3x=-4x+8 | | 12x^2-25x+2=0 | | 8*3(3+2)-6= | | 2.5x=15.2 | | -94-2x=5x+32 |